2002
DOI: 10.1016/s0001-2092(06)61460-9
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Laparoscopic Nissen Fundoplication

Abstract: Gastroesophageal reflux disease affects more than 40% of Americans, causing heartburn and reflux of gastric contents into the esophagus when bending or lying down. Lifestyle modification, such as weight loss and a diet rich in protein and low in fat and glucose, should increase the patient's resting lower esophageal sphincter pressure. Avoiding exacerbating substances, such as mint, chocolate, alcohol, and tobacco, also may reduce symptoms. Medications may be prescribed to reduce persistent symptoms, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…3,4 However, in a review of all reported adult Morgagni hernia repairs, there were no case reports of outpatient repair though other laparoscopic procedures and some open abdominal hernia repairs have been done safely in an outpatient setting with reduced costs and higher patient satisfaction. 3,[5][6][7] So, here, we present a case of a laparoscopic primary repair of a Morgagni hernia that did not require overnight hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, in a review of all reported adult Morgagni hernia repairs, there were no case reports of outpatient repair though other laparoscopic procedures and some open abdominal hernia repairs have been done safely in an outpatient setting with reduced costs and higher patient satisfaction. 3,[5][6][7] So, here, we present a case of a laparoscopic primary repair of a Morgagni hernia that did not require overnight hospitalization.…”
Section: Introductionmentioning
confidence: 99%